2011
DOI: 10.1007/s00330-011-2147-x
|View full text |Cite
|
Sign up to set email alerts
|

The value of dual-energy CTA for control of surgically clipped aneurysms

Abstract: DE-CTA provides better image quality with fewer disturbances by clip artefact, a satisfying evaluation of remnant aneurysm necks and the surrounding vessels. As this method is easily performed and readily accessible with fast image post-processing using BR it provides an opportunity to avoid invasive DSA in the evaluation of suspected aneurysm rests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
4
2
1
Order By: Relevance
“…A study investigating the potential value of DE-CTA imaging for surgically treated IAs using a 64-row dual-source CT scanner system reported significantly lower artifacts and/or superior visualization of the clipped IAs and branching arteries based on subjective image evaluation [35]. In contrast to this study, we investigated and found objective imaging superiority of DE-CTA over SE-CTA by quantifying the artifact volume.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…A study investigating the potential value of DE-CTA imaging for surgically treated IAs using a 64-row dual-source CT scanner system reported significantly lower artifacts and/or superior visualization of the clipped IAs and branching arteries based on subjective image evaluation [35]. In contrast to this study, we investigated and found objective imaging superiority of DE-CTA over SE-CTA by quantifying the artifact volume.…”
Section: Discussioncontrasting
confidence: 42%
“…Thus, our data are in accordance with those reported by Dolati et al [36] supporting the reported accuracy of DE-CTA to detect IA remnants of <2 mm and parent vessel patency in clipped IAs. Both Fahrendorf et al [35] and Dolati et al [36] did not report on the value of DE-CTA after endovascular treatment of IAs, and even though beam-hardening artifact volumes were significantly reduced by DE-CTA in our study, the overall image quality of DE-CTA for evaluation of IAs and parent arteries after endovascular repair seems to have no benefit over MRA as a noninvasive follow-up image modality. Recent data on a novel MRA algorithm that contains an ultrashort echo time combined with an arterial spin-labeling technique (silent MRA) have demonstrated the value of MRA as an alternative to catheter angiography, not only for evaluating IA occlusion rate but also for visualization of flow in intracranial stents after stent-assisted coil embolization [37].…”
Section: Discussioncontrasting
confidence: 39%
“…Overall, the risk of (re-) rupture in these cases remains unclear for now. Thus, significant consequences for patients may be repetitive control MRI/dual source energy CT [7] or invasive angiography with potential side effects or even a re-treatment of the lesion. Besides the risk of repair, these data have to be balanced against the natural history of unruptured MCA aneurysms as well.…”
Section: Occlusion Ratesmentioning
confidence: 99%
“…Diese sind aber bisher noch nicht in die Routinediagnostik integriert [24]. Die Beurteilung clipversorgter Aneurysmen ist mit der zunehmend verfügbaren Dual Energy-CT-Technik schon sehr gut möglich [25]. Mit der geeigneten technischen Ausstattung, insbesondere mit geeigneten Rekonstruktionsalgorithmen, ist die CTA der 3D-DSA heute sowohl in der Detektion von Aneurysmen als auch zur Therapieindikationsstellung und zur Therapieplanung ebenbürtig.…”
Section: Die Rolle Der Computertomografieunclassified